Kecenderungan Gaya Kepemimpinan Kepala SMK Queen Al Falah Mojo Perspektif Teori Managerial Grid of Leadership Styles - Dofir (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
This article analyzes the leadership style tendencies of the principal of Queen Al Falah Mojo managerial grid of leadership styles theori a theoretical perspective. A leader of an educational institution must be able to influence the people he leads, can unite subordinates, and achieve a predetermined goal in the organization. The method used is a qualitative approach with a descriptive method. The results of this study include; The behavioral orientation of the Principal of Queen Al Falah Mojo Vocational School has the same high attention to subordinate individual relationships and to the achievement of goals, while the leadership style tendency to apply a democratic style that is relatively equal in both attention to the cohesiveness of subordinates and the achievement of the tasks or goals of the school organization.